Evaluating Small and Medium-Sized Enterprises’ Resilience in South Africa - Msomi Thabiso Sthembiso; Olarewaju Odunayo Magret (Folia Oeconomica Stetinensia)
Small and medium-sized enterprises (SMEs) face unique challenges that require a deeper understanding of the mechanisms that contribute to their resilience in a dynamic economic landscape.